Perceraian Akibat Pandemi ditinjau dari Hukum Islam Indonesia - Rina Septiani (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
This paper discusses divorce caused by a pandemic seen from Islamic law in Indonesia, the breakup of a marriage is something that is hated by Allah SWT, but in the Islamic legal regulations compiled into the KHI it explains several things that divorce may occur, one of which is quarrels. continuously, this research. will focus on divorces that occurred due to the pandemic that hit especially in Indonesia. This study uses a literature study with a normative-comparative analysis approach, using qualitative data to secondary data as an analysis. This study found that a prolonged pandemic has caused some people to lose their jobs so that they are no longer able to support their families, both wives and husbands are not ready to face this, then divorce is caused by the current pandemic. This is allowed because there is an element of incompatibility between the two parties and if it continues it will have a bad impact on both.